Endoscopic stenting for colorectal cancer obstruction as a bridge‐to‐surgery strategy. (29th May 2020) - Lovero, Rosa; Losurdo, Giuseppe; La Fortezza, Rosa Federica; Spirito, Fulvio; Di Leo, Alfredo; Andriulli, Angelo; Gentile, Marco
Abstract: Background: Acute obstructive colorectal cancer requires prompt decompression commonly by emergency surgery (ES). However, self‐expanding metal stents (SEMS) have been increasingly used as a bridge‐to‐surgery (BTS) strategy. Materials and methods: In an 8‐year period, consecutive patients with acute left‐sided colonic obstruction, due to locally advanced colorectal cancer, underwent ES or SEMS implantation. We evaluated technical/clinical success of SEMS, adverse events, and overall (OS) and disease‐free survival (DFS) of the two therapeutic options. Results: Forty‐five patients underwent ES (n = 23) or SEMS (n = 22). The two groups were comparable for sex, age, ASA score and cancer site/stage. Technical and clinical successes of SEMS were 100% and 72.7%, respectively. Clinical success correlated with neutrophil‐lymphocyte ratio (NLR) at baseline (OR = 0.65, 95% CI 0.43‐0.98, P = .04). SEMS allowed primary anastomosis in the 45.5% of cases (0% in ES). SEMS implantation allowed a higher rate of surgery carried out by a laparoscopic approach: 36.4% vs 13.0% in ES. Performance of a definitive stoma and complications were similar. Median OS (34 in SEMS; 45 in ES, P = .33) and DFS (36 in SEMS; 35 in ES, P = .35) did not differ between the two groups. At univariate analysis, DFS was positively associated with primary anastomosis (HR = 2.44, 95% CI 1.4‐16.6, P = .04) and laparoscopic surgery (HR = 8.33, 95% CI 1.08‐50, P = .04), and inversely associated with a NLR > 3.6 (HR = 0.59, 95% CI 0.16‐0.92, P = .03). At multivariate analysis, no feature retained an independent predictive power. Conclusion: SEMS is an effective and safe procedure, equivalent to emergency surgery in terms of complications, OS and DFS, providing the chance of a primary anastomosis in the majority of patients.